2015
DOI: 10.1007/s10725-015-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PHYB in resistance to Cucumber mosaic virus in Nicotiana tabacum

Abstract: Plants are exposed to a diversity of environmental stresses throughout their life cycles and need to constantly regulate their developmental and physiological processes to respond various external stimuli. It is well known that the interaction between light and plant defence is multifaceted and complicated. Here, the recombinant vector pRNAi-LIC-PHYB was used for achieving tobacco (Nicotiana tabacum) PHYB defective mutant via the Agrobacterium-mediated transformation method. Furthermore, we investigated molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In this paper, a study was conducted to investigate the role of phytochromes in the interaction between N. tabacum and CMV. The results indicate that phytochromes phyA and phyB play a crucial role in the development of the defence ability in N. tabacum induced by CMV, which is somewhat consistent with previous suggestions that phytochromes are essential for plants to induce complete defence responses against attacks from various pathogens (Jeong et al ., ; Kazan & Manners, ; Xie et al ., ; Li et al ., ). Based on the results from tobacco phytochrome mutants, it is also hypothesized that a heightened sensitivity to CMV in phyA or phyB mutants might occur by repressing the SA‐mediated defence pathway in N. tabacum .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this paper, a study was conducted to investigate the role of phytochromes in the interaction between N. tabacum and CMV. The results indicate that phytochromes phyA and phyB play a crucial role in the development of the defence ability in N. tabacum induced by CMV, which is somewhat consistent with previous suggestions that phytochromes are essential for plants to induce complete defence responses against attacks from various pathogens (Jeong et al ., ; Kazan & Manners, ; Xie et al ., ; Li et al ., ). Based on the results from tobacco phytochrome mutants, it is also hypothesized that a heightened sensitivity to CMV in phyA or phyB mutants might occur by repressing the SA‐mediated defence pathway in N. tabacum .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies have shown that phytochromes also act as key mediators of a plethora of diverse biotic and abiotic stresses (Carvalho et al ., ). Previous studies have suggested that phyB is essential for the defence strategies of N. tabacum against CMV (Li et al ., ). The results of the present study show that mutation of phyA also compromises the resistance ability of N. tabacum induced to CMV attack.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The phytochrome (phy) family of receptors played a major role in perceiving red (R) (Rangani et al 2015) and far-red (FR) light (Li et al 2015), which carried information on the availability of photosynthetic energy and the proximity of neighboring plants (Chen and Chory 2011). Therefore, they were essential for the regulation of developmental processes from seed germination to the timing of reproductive development (Franklin and Quail 2010).…”
Section: Gene Ontology Enrichment Analysis Of Hs-regulated Genesmentioning
confidence: 99%